Pengaruh Kesan dukungan organisasi dan Keterampilan interpersonal terhadap Motivasi Berprestasi Karyawan PT Gloster Furniture - Eli Retnowati (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Humans play an important role in the industry for this reason it requires high achievement motivation which is influenced by the perception of organizational support and good interpersonal women will produce increased performance results and organizational goals are achieved. This study аims to determine the effect of perceived organizational support on achievement motivation; to determine the effect of interpersonal skills on achievement motivation; to determine the effect of perceived organizational support and interpersonal ability simultaneously on achievement motivation. The population in this study were employees of PT Gloster Furniture, a sample of 100 respondents. The analysis technique is multiple linear regression with the help of the SPSS Ver 26. The findings of the research show that there is a positive and significаnt influence on the perception of organizational support and interpersonal ability on achievement motivation.